2010
DOI: 10.1577/t08-148.1
|View full text |Cite
|
Sign up to set email alerts
|

Movement and Mortality of Adult Brown Trout in the Motupiko River, New Zealand: Effects of Water Temperature, Flow, and Flooding

Abstract: Abstract.-Management of the effects of water quality and flow on fisheries requires an understanding of the factors that control fish movements. We used radiotelemetry to monitor the movements of adult brown trout Salmo trutta in a New Zealand river over 11 months (September 2004 to August 2006 and linked those movements to the changes in flow and water temperature. Individual fish moved up to 41 km during the study. However, most fish moved less than 1 km. All of the trout that showed little movement through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 61 publications
(89 reference statements)
4
24
0
Order By: Relevance
“…Similar patterns of increased movement and the use of thermal refugia when ambient temperatures are outside of an optimal bioenergetic range have been observed in brown trout (Young et al 2010), adult Chinook salmon O. tshawytscha (Goniea et al 2006), and adult steelhead (anadromous rainbow trout; Keefer et al 2009). Many studies have shown that brook trout and other salmonids use coldwater sources, such as tributaries, seeps, and groundwater upwellings, to avoid thermal (both upper and lower) stress (Baird and Krueger 2003;Goniea et al 2006;Breau et al 2007;Young et al 2010).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Similar patterns of increased movement and the use of thermal refugia when ambient temperatures are outside of an optimal bioenergetic range have been observed in brown trout (Young et al 2010), adult Chinook salmon O. tshawytscha (Goniea et al 2006), and adult steelhead (anadromous rainbow trout; Keefer et al 2009). Many studies have shown that brook trout and other salmonids use coldwater sources, such as tributaries, seeps, and groundwater upwellings, to avoid thermal (both upper and lower) stress (Baird and Krueger 2003;Goniea et al 2006;Breau et al 2007;Young et al 2010).…”
Section: Discussionsupporting
confidence: 54%
“…Many studies have shown that brook trout and other salmonids use coldwater sources, such as tributaries, seeps, and groundwater upwellings, to avoid thermal (both upper and lower) stress (Baird and Krueger 2003;Goniea et al 2006;Breau et al 2007;Young et al 2010). During the early summer, trout in the main stem also showed a higher affinity for movement when temperatures were much lower than 14 • C. This further demonstrates the importance of stream temperature for influencing trout behavior and selection of optimal habitat in the upper Shavers Fork watershed.…”
Section: Discussionmentioning
confidence: 82%
“…There are no physical barriers within the studied area, and the largest distance, 3.1 km, was between the SO and TI-3 sections. This distance was within the observed range for resident brown trout dispersal (Young et al, 2010) and we thus consider there is no impediment to fish movement. All localities except the main river (SO) are included in the protected area of ''Planes de Son'', and not stocked with hatchery fish according to official records.…”
Section: Study Area and Sampling Of Collectionssupporting
confidence: 55%
“…Results from some studies have supported the notion that movement of resident individuals is limited (Knouft & Spotila, 2002;Rodríguez, 2002) whereas others have detected substantial dispersal (reviewed by Gowan et al, 1994;Höjesjö et al, 2007). Recently, Young et al (2010), using radiotelemetry and ecological data, observed little movement for most of the so called ''resident'' individuals, although large displacements up to 40 km were observed for a few. However, experimental limitations of the methods used in these studies call into question the generalization of their conclusions.…”
Section: Introductionmentioning
confidence: 94%
“…Masu salmon did not decline in abundance after the floods, suggesting their high resistance to flood disturbance. In contrast, the abundance of adult rainbow trout decreased dramatically, which was similar to previous observations of other salmonid species (Carline & McCullough 2003;Sato 2006;Young et al 2010). In addition, the fact that we could not capture age-1 rainbow trout in 2011 suggested that most of the 0C rainbow trout in 2010 were displaced by the debris flow in 2010.…”
Section: Discussionsupporting
confidence: 89%